PROSES PENGEMBANGAN KEWIRAUSAHAAN DI PERGURUAN TINGGI MELALUI KEWIRAUSAHAAN INTELEKTUAL - Beni Dwi Komara; Aries Kurniawan; Heri Cahyo Bagus Setiawan (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Entrepreneurship and intellectuality are often believed to be two different poles. However, the concept of Intellectual Entrepreneurship provides awareness that the work of intellectuals can not only increase the height of the stack of books in the library, but also collaborate with other stakeholders by turning the creativity presented in science into a source of innovation and strategies for sustainable economic & business development. This study aims to determine whether intellectual entrepreneurship has been carried out by universities and how the process of intellectual entrepreneurship in universities can accelerate entrepreneurial development. The research was conducted using descriptive qualitative methods at the University of Muhammadiyah Gresik. The results show that Intellectual Entrepreneurship has been implemented in higher education, indicated by the existence of creative scientific work that has IPR and has collaborated with stakeholders to become a business solution for the community. The process of developing entrepreneurship in higher education through Intellectual Entrepreneurship is as follows: 1.Teaching mastery of entrepreneurial skills including Self-Management, Learning Agility, Business Analysis Acuity, Innovative Creative Research, Financing Management, and IPR, 2. Creating a business culture in the campus environment and 3. Encouraging strategic collaboration with stakeholders such as the community, other universities, research institutions, business consultants, companies, Bumdes, MSMEs and the government.